Avatarian embodiment in Indigenous Futurisms 4D: the intersemiosis of intercultural encounters. (2nd January 2023) - Fawzy, Rania Magdi; El Shazly, Reham Farouk
ABSTRACT: Drawing on VR affordances and its relevant discourse of embodiment, immersion and engagement, Indigenous Futurisms (IF) challenges mainstream stereotypes of indigenous cultures. This article explores how the VR movie Crow: The Legend mediates an intercultural experience of IF. The framework proposed for understanding the virtually-mediated IF intercultural experience is grounded in the integration of SF-MDA and postphenomenology. The suggested theoretical integration interprets the VR embodied affordances of navigation, body movement, and hand gestures. The dialogue established in Crow between the interactants and VR technology unravels the cultural particularities of futurisms' notions of 'non-linear temporality, ' 'selfdetermination, ' 'self-discovery, ' 'selflessness' and 'diversity'.